Protecting nature on private land using revolving funds: Assessing property suitability. (April 2018) - Hardy, Mathew J.; Bekessy, Sarah A.; Fitzsimons, James A.; Mata, Luis; Cook, Chris; Nankivell, Alex; Smillie, Kate; Gordon, Ascelin
Abstract: Protecting biodiversity on private land is an important and growing part of global conservation efforts. Revolving funds are used by conservation organisations to buy, resell and permanently protect private land with important ecological values. By reinvesting proceeds from sales in additional properties, revolving funds offer a potentially cost-effective way to protect biodiversity. Their success requires managers to choose properties that can be resold and recover costs, with resale outcomes having consequences for subsequent acquisitions. However, revolving fund property selection is a multi-dimensional decision, influenced by various ecological, social and financial considerations. In conjunction with revolving fund managers, we developed a Bayesian Belief Network (BBN) to understand which factors they consider to be the most influential on a propertyʼs suitability for acquisition, and how much to pay for it. Sensitivity analysis revealed that managers perceive property suitability to be heavily influenced by the threat to the propertyʼs ecological values, the acquisition and ongoing management costs, and finding alternative options for protection. Amenity values were seen to heavily influence property resale. Threat and alternative options influence how much to pay, but most influential was the balance of the fund when the purchasing decision is made. Our results suggest managers are taking a low risk approach to property selection. Opportunities may exist to apply revolving funds to higher risk properties otherwise difficult to conserve, provided the need for resale is still met. Ensuring revolving funds target properties with suitable attributes could increase the contribution of this tool to conserving biodiversity on private land. Graphical abstract: Unlabelled Image Highlights: Revolving funds are used by some conservation organisations to permanently protect private land. Selecting suitable properties for this tool is challenging but important for outcomes. Via a probabilistic reasoning model we elicited practitioner knowledge about suitability. The main influences were financial return, ecological threat, and likelihood of resale. Our study provides greater clarity on property suitability for revolving fund managers.